(untitled) (American Journal of Islam and Society, 2005)
The Muslim ummah, as a world community, faces many challenges at the threshold of the new century. The fateful event of 9/11 has revealed yet another facet of the problems plaguing Muslim society: the existence of radical, or what some media have labeled “militant,” Muslim groups. Despite the Muslim world’s condemnation of the 9/11 terrorist attack, the United States considered itself the victim and thus launched its “war against terrorism” against the alleged perpetrators: the Taliban and al-Qaeda. Iraq, which was alleged to be building weapons of mass destruction (WMDs) and assisting al-Qaeda, became the second target. Iran would have become the immediate third target if the international community had supported the Bush administration’s unilateral declaration of war against Iraq. But it did not, for the allegations could not be proven. Unfortunately, this new American policy has not helped to curb aggression or terrorism; rather, it has caused radical groups to run amok and indulge in even more acts of terrorism in Israel, Palestine, Indonesia, Turkey, Spain, Iraq, and Saudi Arabia. The 9/11 tragedy has caused the West to hold more negative images of Muslims and Islam and has made life more difficult for Muslims living in the West. In response, anti-Americanism has grown throughout the world, particularly in the Muslim world.1 September 11 seemed to provide certain Muslim governments with the license to combat terrorism on the local front more rigorously. This action heightened the conflicts between local Muslims and the ruling governments, as in the case of General Musharraf of Pakistan, who decided to cooperate with Washington in its “war against terrorism” by providing bases for American forces. After 9/11, Egypt, Tunisia, and Malaysia all received repeated praise from Washington for their experience and seriousness in combating terrorism and joining the alliance against it, despite their track record on, for example, human rights violations vis-à-vis the ruling elites’ ...